2011
DOI: 10.1016/j.jhealeco.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Is employer-based health insurance a barrier to entrepreneurship?

Abstract: The focus on employer-provided health insurance in the United States may restrict business creation. We address the limited research on the topic of "entrepreneurship lock" by using recent panel data from matched Current Population Surveys. We use difference-indifference models to estimate the interaction between having a spouse with employer-based health insurance and potential demand for health care. We find evidence of a larger negative effect of health insurance demand on business creation for those withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…The overall economic environment and governmental policies play a crucial role and govern these opposing forces (Fairlie et al, 2011). Opportunity entrepreneurs may spend less and delay investments during high taxation and recessions, while they are also more likely to start a business when tax policy and government size are more conducive; necessity entrepreneurs, on the other hand, are forced out of the labor force and into entrepreneurship because of adverse economic conditions (Shiller, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The overall economic environment and governmental policies play a crucial role and govern these opposing forces (Fairlie et al, 2011). Opportunity entrepreneurs may spend less and delay investments during high taxation and recessions, while they are also more likely to start a business when tax policy and government size are more conducive; necessity entrepreneurs, on the other hand, are forced out of the labor force and into entrepreneurship because of adverse economic conditions (Shiller, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has found that individuals lacking health insurance are less likely to be self-employed (Fairlie, Kapur, & Gates, 2011;Gumus & Regan, 2015;Holtz-Eakin, Penrod, & Rosen, 1996;Wellington, 2001). This finding has given support to the job lock hypothesis that posits the loss of employer provided health insurance inhibits potential entrepreneurial employment.…”
Section: Assets Of Entrepreneursmentioning
confidence: 86%
“…Indeed, older self-employed adults are less likely to be part of workplace pension and health insurance programs [13]. These barriers may be too expensive to overcome, as evidenced by the fact that rates of entrepreneurship increase after Americans turn 65, the general eligibility age for joining Medicare, the universal health insurance program for older Americans [75]. Indeed, scholars have called for increased levels of social protections—such as unemployment and “food stamp” (SNAP) benefits for entrepreneurs—to make it easier for potential entrepreneurs of all ages to begin their work [73].…”
Section: Discussionmentioning
confidence: 99%